2019
DOI: 10.1093/scan/nsz024
|View full text |Cite
|
Sign up to set email alerts
|

Wired to be connected? Links between mobile technology engagement, intertemporal preference and frontostriatal white matter connectivity

Abstract: Youth around the world are increasingly dependent on social media and mobile smartphones. This phenomenon has generated considerable speculation regarding the impacts of extensive technology engagement on cognitive development and how these habits might be ‘rewiring’ the brains of those growing up in a heavily digital era. In an initial study conducted with healthy young adults, we utilized behavioral and self-report measures to demonstrate associations between smartphone usage habits (assessed both subjective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…Moreover, diminished cortical thickness of (amongst others) the ventral LPFC and TPJ across adolescence have been related to a lack of impulse control ( Pehlivanova et al, 2018 ), a characteristic that has often been related to social media use. Indeed, Wilmer and Chein, 2016 , Wilmer et al, 2019 reported that individual differences in smartphone use were associated with impulsivity as measured with a delay discounting task. Moreover, they found that stronger structural connectivity between ventral striatum and MPFC was related to more engagement with smartphones, whereas connectivity between ventral striatum and dorsal LPFC was related to less engagement ( Wilmer et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, diminished cortical thickness of (amongst others) the ventral LPFC and TPJ across adolescence have been related to a lack of impulse control ( Pehlivanova et al, 2018 ), a characteristic that has often been related to social media use. Indeed, Wilmer and Chein, 2016 , Wilmer et al, 2019 reported that individual differences in smartphone use were associated with impulsivity as measured with a delay discounting task. Moreover, they found that stronger structural connectivity between ventral striatum and MPFC was related to more engagement with smartphones, whereas connectivity between ventral striatum and dorsal LPFC was related to less engagement ( Wilmer et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Wilmer and Chein, 2016 , Wilmer et al, 2019 reported that individual differences in smartphone use were associated with impulsivity as measured with a delay discounting task. Moreover, they found that stronger structural connectivity between ventral striatum and MPFC was related to more engagement with smartphones, whereas connectivity between ventral striatum and dorsal LPFC was related to less engagement ( Wilmer et al, 2019 ). Moreover, Paulus and collogues (2019) used a group factor analyses to investigate latent variables that relate to social media activity and found that four group factor analyses explained 37% of the variance between social media and structural brain indices (cortical thickness, sulcus depth and volume).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same group of smartphone addicts studied in Schmitgen et al (2020) also evinced weaker coordination between the dmPFC and the left PPC, and between the anterior insula and the right lateralized PPC (Horvath et al, 2020). Other recent work in heavy and excessive smartphone users has likewise indicated weaker intra-network connectivity in the FP and CO networks (Chun et al, 2020), and decreased functional (Chun et al, 2020) and structural (Wilmer et al, 2019) connectivity between key centers of the brain's control networks and the ventral striatum (VS), a region of the brain where mesolimbic dopamine is released to signal the value of potential rewards. Thus, studies of brain activity and connectivity suggest that individuals who are more enmeshed with digital media also have a harder time (or need to devote more effort) initiating and sustaining self-regulatory processes, and may not be as facile at controlling responses to appetitive and potentially rewarding cues.…”
Section: Digital Media and The Brain's Control And Attention Networkmentioning
confidence: 72%
“…Eslami et al (2018) provide a protocol for exhibit-driven exposure to stimulate qualitative depth research to surmount the issue of consumer ignorance of the process of analytics. Neuroscience methods may also have a place in mapping the cognitive morphology during variant lab-based purchase tasks on different cohorts with differential use of smart technology (see Braeutigam et al, 2019 or Wilmer et al, 2019). Mobile diaries are another possibility; Lovett and Peres (2018) examine the efficacy of this form of data capture in a consumer research context.…”
Section: Theory Development Corroboration and Empirical Deploymentmentioning
confidence: 99%